2014
DOI: 10.4028/www.scientific.net/amr.1039.383
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Algorithm of Tool Radius Compensation in Fast Tool Servo Machining of Microlens Arrays

Abstract: This paper analyzes the tool path generation of the microlens arrays by the single point diamond (FTS) turning,while focuses on the algorithm of tool radius compensation. Firstly, the mechanism of the fast tool servo machining process is introduced. Secondly, the tool path generation for FTS is calculated. The algorithm of tool radius compensation and the form error of the microlens is analyzed. Subsequently, the transitional zone is research, base on the algorithm of tool radius compensation, the optimized al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…17 Ding et al analysed the tool path of the microlens array produced by FTS turning, and focused on the tool radius compensation algorithm. 18 Yu proposed a method for optimizing the path of FTS diamond turning tools based on analytical description of nonuniform rational B-spline description. 19 The study found that the tool path planning of most FTS and its derived machining technologies have one thing in common.…”
Section: Introductionmentioning
confidence: 99%
“…17 Ding et al analysed the tool path of the microlens array produced by FTS turning, and focused on the tool radius compensation algorithm. 18 Yu proposed a method for optimizing the path of FTS diamond turning tools based on analytical description of nonuniform rational B-spline description. 19 The study found that the tool path planning of most FTS and its derived machining technologies have one thing in common.…”
Section: Introductionmentioning
confidence: 99%